OBTAINING LIQUID NITROGEN FERTILIZERS WITH FEROCENE IN THEIR STRUCTURE (Scientific journal of the Fergana State University, 2023)
The article presents some spectral analysis of mineral fertilizers and their types, the production of liquid nitrogen fertilizers containing ferrocene.